145k views
5 votes
Please solve this question. ​

Please solve this question. ​-example-1
User Chao Zhang
by
6.2k points

1 Answer

3 votes

Answer: see proof below

Explanation:


x^a=y^b=z^c\ =k\\

Then
x^a=k\qquad \rightarrow \qquad x=k^{(1)/(a)}

and
y^b=k\qquad \rightarrow \qquad y=k^{(1)/(b)}

and
z^c=k\qquad \rightarrow \qquad z=k^{(1)/(c)}

y³ = x · z


(k^{(1)/(b)})^3=k^{(1)/(a)}\cdot k^{(1)/(c)}\\\\k^(3)/(b)}=k^{(1)/(a)+(1)/(c)}\\\\\\\bold{(3)/(b)=(1)/(a)+(1)/(c)}\quad \checkmark

Please solve this question. ​-example-1
User Grae Kindel
by
6.2k points